Anterior Open Bite Treatment in the Mixed Dentition: a Brief Review and Case Report - Mendonça, Marcos Rogério de; Ruiz, Ana Laura Ribeiro; Ferreira, Mayra Fernanda (ARCHIVES OF HEALTH INVESTIGATION, 2023)
Anterior open bite (AOB) is a vertical plane malocclusion characterized by a negative vertical overbite and can be classified according to its nature: dentoalveolar or skeletal. The dentoalveolar anterior open bite (DAOB) occurs in individuals who have a good relationship between the bone bases and its etiology is associated with environmental factors. DAOBS´s treatment tends to have a favorable prognosis and it’s up to the dentist to choose the most adequate method in each case. Thus, the objective of this study is to present a case report of DAOB. Female patient of 6 years old attended the Preventive Orthodontics Clinic of the Faculty of Dentistry of Araçatuba - UNESP, having as main complaint “open bite”. In the anamnesis the patient revealed that used a pacifier and presented a digital sucking habit. The patient was in the first transitional period of mixed dentition with permanent incisors and first molars partially erupted. The diagnosis was of Angle Class I malocclusion with dentoalveolar anterior open bite and dentoalveolar anterior crossbite of the deciduous right maxillary canine. The bi-helix with crib appliance was installed and the patient was oriented to perform myofunctional exercises daily. This therapeutic protocol represents an efficient and effective approach for the correction of DAOBs providing improved aesthetics, social well-being and a more appropriate and correct occlusion that allows oral functions (deglutition, speech and chewing) to work properly. The results acquired through this treatment are essentially of dentoalveolar nature.